Estimation of bare soil surface temperature from air temperature and soil depth temperature in a tropical station (2011)
Soil surface temperature has critical influence on climate, agricultural and hydrological activities since it serves as a good indicator of the energy budget of the earth’s surface. Two empirical models for estimating soil surface temperature from air temperature and soil depth temperature were developed. The coefficient of determination (R2) of soil surface temperature from the air temperature model ranged from 0.92 - 0.99, while the mean absolute error (MAE) and root mean squared error (RMSE) ranged from 0.5 - 2.48 and 0.77 - 2.630C respectively. For the soil depth model, the R2 value ranged from 0.75 - 0.96, MAE ranged between 1.05 and 4.94, while RMSE ranged from 1.28 - 5.25. Both models performed well on days of year (DOYs), under similar prevailing weather conditions during the model training period.